The Role of Service Staff in Digitalization at PT. PLN (Persero) ULP Rungkut - Afrianti, Athika Dewi; Nugroho, Rusdi Hidayat (CV. Lenggogeni Data Publishing, 2024)
This study aims to analyze the role of service staff in supporting digitalization at PT PLN (Persero) Rungkut Customer Service Unit (ULP). In the digitalization process, service staff play a strategic role as the spearhead of interaction with customers, especially in implementing technologies such as the PLN Mobile application and smart metering. This research uses various references from relevant journals to understand how service staff can contribute to the success of digital transformation in the utility sector. This study concludes that the success of digital transformation in PLN ULP Rungkut is highly dependent on the ability of service staff to carry out their roles. Therefore, PLN needs to improve training for staff, provide adequate infrastructure, and educate customers to support the effective adoption of digital services.